Hospitalized Children Continue to Report Undertreated and Preventable Pain - Kathryn A Birnie; Christine T Chambers; Conrad V Fernandez; Paula A Forgeron; Margot A Latimer; Patrick J McGrath; Elizabeth A Cummings; G Allen Finley (Pain Research and Management)
BACKGROUND: Published reports of substantial rates of moderate to severe pediatric inpatient pain tend to overlook lower-intensity pain that may be clinically significant.